The Relationship between Job Demands and Positive Emotions on Work Engagement among Academic Staff in Algeria: A Conceptual Paper - Elkheloufi, Abderrahmane; Yean, Tan Fee (South Asian Journal of Social Sciences and Humanities, 2022)
An organization requires employees that are full of energy and interpersonal trust; they are passionate and enthusiastic about their jobs and are completely focused on their professional objectives. In other words, an organization requires a higher level of work engagement among its employees. As a result, it is becoming increasingly crucial for organizations to design in a way that allows employees to unleash their full potential and become more engaged at work. Organizations also need employees that are emotionally invested in their jobs and willing to go above and beyond to help their organizations succeed. The present study examines the link between job demands, positive emotions, and work engagement using the Broaden-and-Build theory and the job demands-resources model of work engagement. A cross-sectional poll was performed with more than 364 academicians from Algerian public institutions who were chosen using stratified random sampling. The current paper confirms previous findings on the relationship between job demands, positive emotions, and work engagement. The latest study backs up prior research on the link between job demands, positive emotions, and work engagement. As a consequence of these findings, managers may be able to boost employees’ work engagement by focusing on people with lower job demands and more positive emotions.